The Success of the Baitul Tahfidz Al-Qur'an Program: An Evaluation Study at Baitul Jannah, Bandar Lampung - Pramida, Evita; Ayu, Sovia Mas; Dermawan, Oki; Yetri (Journal of Advanced Islamic Educational Management, 2024)
In T.A 2022/2023, six out of nine students at Baitul Jannah IT Junior High School Bandar Lampung successfully achieved the target of memorizing the Qur'an or passed the Baitu Tahfidz program, covering 66.6% of the total participants. This study aims to evaluate the program using a qualitative method with a CIPP (Context, Input, Process, Product) evaluation approach. Data were collected through interviews, observations, and document analysis. The evaluation results showed that in the context dimension, the Baitu Tahfidz program received full support from the school and the surrounding community and was an integral part of the school's vision and mission. In the input dimension, it was found that human resources were still minimal, infrastructure was inadequate, and the curriculum needed improvement. In the process dimension, the implementation of the program is according to plan with five meetings per week, but the time to memorize only one hour per day is considered insufficient. In the product dimension, the achievement of memorization targets has not been maximized, with 13 out of 18 ninth grade students passing the final exam. Nevertheless, the program succeeded in shaping the character of students who are noble, religious, and love the Qur'an. This study provides a comprehensive evaluation that can be the basis for improvement and development of the Baitu Tahfidz program in the future.